Malaria in infants aged less than six months - is it an area of unmet medical need? - D’Alessandro, Umberto (BioMed Central, 2012)
Despite the protection provided by several factors, including maternal antibodies, the burden of malaria in young infants may be higher than previously thought. Infants with congenital or neonatal malaria may have a different clinical presentation than older children, and diagnosis may be confused with other neonatal diseases due to an overlap of clinical manifestations. In addition, there is little information on the use of artemisinin-based combination therapy in young infants. There is the need for a more accurate estimate of the parasite prevalence and the incidence of clinical malaria in infants under 6 months old, as well as a better characterization of risk factors, pharmacokinetic profiles, safety and efficacy of currently available anti-malarial treatments, in order to develop evidence-based treatment guidelines for this population.